Gen Z and Millenial Challenges: Personal Finance on Digital Age - Paramitalaksmi, Ratri; Budiantara, Martinus (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to find differences in factors that affect Personal Finance, including Financial Literacy and Financial Technology Inclusion between Gen Z and Millennials, especially in the Special Region of Yogyakarta. The population in this study is Gen Z and Millennials in the Special Region of Yogyakarta. The data used is primary data the form of questionnaire results and in-depth interviews with Gen Z and Millennials, Yogyakarta. The data processing in this study uses SPSS. The results of this study show that Financial Literacy and Lifestyle of Millennials and Gen Z have a significant influence on their Personal Finance, but Financial Technology Financial Inclusion does not have a significant influence on their Personal Finance. This research is important to understand what factors influence the younger generation in managing their personal finance, especially in this digital era where there are many challenges in managing personal finance.